(3QSGFd GdZeQi aj GdUfYI GdEdgjIs - (3eMeO GdYeQj , eMeO GdZeQj GdMSfj GdTGaYj,J (B1124 (3g` s
(3ChdgG (B:s
(3GYde jG CNj habc Gddg JYGdi Cf GdEfSGf EPG YQa GdMLQ GdeTGQ Edjg abO GSJQGM ef GdHMQ GdPi dGSGMd dg s
(3BNQgG (B:s
(3hgh GdYTQI CfhGY GdJi PcQgG GdMcje hGdSdGe Bcjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B113s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WHjYI (B323) s
Keywords: (3GdcjejGA h GdWHjYjGJs